EBA-SP BERDASARKAN PRINSIP SYARIAH - Syapar Alim Siregar (Institut agama islam negeri Padangsidimpuan, 2021)
EBA is an investment intrumnet obtained from securitieus that are written in paper in the form of documents and in the form of letters where the results of participation are in accordance with Islamic shariah and do not violate on the law, and only operate in the middle or secondary market in Islamic banking as a means of payment and the public or investorsusing it when the money is no longer stable or maybe the interest rate in one bank is not balanced and has a big influence on investment and state money besides that the partcipationt letter has a lot of of influence not only negative but also positive impacts, for example having coupon offers so that investors are tempted to ionvest and work together. if we look at the income using the capital market this has more related , this has more advantage that will be more related to ojk and provides more goodness, makes everything complete, anda strategy that is in great demand among banks but is basid in sharia by not quoting interest because islam for birds ususry abd interest , the award letter is only issued once so that the negative balance is able to control sharia banking if we look at the case studies in the united states the real studies error is in the understanding of the secondary pattern and the existence of several levels of securities so that it is not balanced and stable and results in a lot of debt.